Implementasi Aplikasi Perangkat Bergerak Pembelajaran Sistem Organ Peredaran Darah pada Tubuh Manusia berbasis Augmented Reality - Muhammad Enowato; Komang Candra Brata; Adam Hendra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
Classic lectures teaching method still often used by teacher in school. The use of assistive media in giving examples is also not used often by teachers. In biology class, many subjects contain an abstract concepts that need to be explained with assistive media. Assistive media that commonly used are a physical props like picture, statue or a doll. But a physical props have a downside because its hard to access by students and lack of giving a real perception to students. Augmented technology can be a solution for a assistive media props substitute which can be accessed easily by students. AR technology can giving a real perception to students with a animated 3D concept. AR mobile apps designed by using a single marker method for giving a easy access for students. Based on test result with 21 respondents, system application got 82,6 with using System Usability Scale method. Effectiveness of the application measured by pre-test and post-test giving an increased value in student learning outcomes of 27,83% from intial average value 65,71 to 84,04